Reference values of inside leg length and inside leg length to stature ratio for Japanese children, 0-12 years of age - Inokuchi, Mikako; Matsuo, Nobutake; Takayama, John I.; Hasegawa, Tomonobu (Annals of Human Biology, 2022)
Large datasets of detailed anthropometric measurements are scarce in children. The Japanese Standard Association 1978-1981 survey provides a rare opportunity to use high quality data from Japanese children. To construct inside leg length (ILL) and inside leg length to stature ratio (ILL/S) reference centile curves for Japanese children. The study sample consisted of 14,825 boys and 14,577 girls age 0-18 years for stature and weight measurements, and 9064 boys and 8796 girls age 0-12 years for ILL measurements, who participated in the 1978-1981 national survey on body sizes. LMS method was used to construct the reference centile curves. The reference centile curves for stature, weight, ILL, and ILL/S were compared to those of British children. The L, M, and S reference values for Japanese children are presented for stature, weight, ILL, and ILL/S. Compared with British children of 0-12 years of age, Japanese children of 0-12 years of age had shorter median stature, shorter median ILL, and shorter median ILL/S. We present the first reference values for ILL and ILL/S in Japanese children. Japanese children had relatively shorter legs compared to British children from infancy.